2021
DOI: 10.1371/journal.pone.0256913
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale urban agriculture: Drivers of growing produce at home and in community gardens in Detroit

Abstract: The desire for fresh, local food has increased interest in alternative food production approaches, such as private small-scale agriculture, wherein households grow their own food. Accordingly, it is worth investigating private agricultural production, especially in urban areas, given that an increasing share of the world’s population is living in cities. This study analyzed the growth of produce at people’s homes and in community gardens, focusing on behavioral and socio-demographic factors. Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 69 publications
4
15
0
Order By: Relevance
“…In contrast, age reduced the odds of being an overall or indoor home gardener across all cities. This aligns with findings from previous studies suggesting that older participants typically have to reduce gardening related physical exertion for their health (Blaine et al, 2010;Grebitus, 2021). Finally, only homeownership increased the odds of being an outdoor gardener across all the cities.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…In contrast, age reduced the odds of being an overall or indoor home gardener across all cities. This aligns with findings from previous studies suggesting that older participants typically have to reduce gardening related physical exertion for their health (Blaine et al, 2010;Grebitus, 2021). Finally, only homeownership increased the odds of being an outdoor gardener across all the cities.…”
Section: Resultssupporting
confidence: 89%
“…The results of this study provide some indication of factors that may inhibit or promote household gardening. In alignment with existing national data (National Gardening Association Research Division, 2021) and city-specific studies (Grebitus, 2021), we found that homeownership increased the odds of gardening across all three cities for the home-based and combination gardening typologies. The association of gardening with homeownership, along with higher education and income, suggests that economic advantage may play a part in an individual's ability to participate in UA.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations